Environmental Management System for Solid Medical Waste Management In Pariaman City Hospital - Raidhatul Fiqra; Yudi Antomi (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to ensure the conformity of medical waste management with the Government Regulation of the Republic of Indonesia Number 7 of 2019 and to determine the implementation process of solid medical waste management of hospitals in Pariaman City, as well as to determine the value of environmental performance based on ISO14001. This research is descriptive qualitative research conducted in February - March 2022 at a hospital in Pariaman City. Sample collection techniques through interviews, filling out environmental performance assessment sheets based on ISO 14001, and documentation. The interview is conducted using a list of questions that have been prepared in advance. Next, descriptive statistical analysis was carried out. The results of this study are The process of solid medical waste management of hospitals in Pariaman City has referred to the Government Regulation of the Republic of Indonesia Number 7 of 2019, although the results are not all appropriate